Identification of the anticancer mechanism of the traditional Chinese medicine compound kushen injection - Cock, I.E. (Pharmacognosy Communications)
Compound Kushen injection (CKI) is a traditional Chinese medicine (TCM) formulation composed of aqueous Sophorae flavescentis Aiton root and Smilax glabrae Roxb. rhizome extracts. It has traditionally been used as an anti-inflammatory drug. It also has antineoplastic activity and has been approved in China to treat several cancers. Despite its chemo- therapeutic usage, the anticancer mechanism of CKI is yet to be fully elu- cidated. This may be due to the reductionist approach of many scientific studies, which are reliant on the isolation and screening of individual extract components. Whilst this is a viable approach for many medi- cines, it is not always effective for complex plant based medicines. TCM generally consists of mixtures of plants/extracts, combined to create a high potency drug. Often, when the individual components are tested in isolation, they have poor efficacy, whereas combinations of components may have additive or synergistic effects. A recent study from an Adelaide University group examined the anticancer mechanism of CKI, 2 making it one of the first studies to report molecular mechanisms for complex mixtures. The study utilised a systems biology approach, which monitors all measurable aspects of the system, rather than focussing on a single bioactivity or morphological change. The research team determined that CKI affected multiple pathways, with cell cycle regulation being particu- larly important. Furthermore CKI was also reported to induce apoptosis in MCF-7 cells via p53 independent mechanisms.